Sarcasm Use In Workplace Communication In American Series House M.D (2012) - Devinta Intan Widyani; Ayunita Leliana (Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study investigates the types of sarcasm used in workplace communication in the American television series House M.D. Season 8 (2012). The study aims to identify and classify sarcastic utterances based on Camp's (2012) typology, which consists of propositional, illocutionary, attributive (lexical), and like-prefixed sarcasm. A qualitative descriptive approach was employed using dialogue transcripts from all 22 episodes of the final season as the primary data source. Data were collected through documentation, verified by comparing the transcripts with the original episodes, and analyzed using the interactive model of Miles et al. (2014), including data condensation, data display, and conclusion drawing. The analysis identified 215 sarcastic utterances representing all four sarcasm types. Propositional sarcasm was the most dominant type (98 occurrences; 45.6%), followed by illocutionary sarcasm (82; 38.1%), attributive sarcasm (30; 14.0%), and like-prefixed sarcasm (5; 2.3%). The findings indicate that workplace communication in House M.D. predominantly employs indirect and context-dependent sarcastic expressions, particularly propositional and illocutionary sarcasm. This study supports Camp's typology and contributes to pragmatic research by illustrating how different linguistic realizations of sarcasm operate within professional workplace discourse.